Unilateralism and multilateralism - Espinosa, Carlos (2016)
In order to redefine the current debate on “multilateralism and unilateralism” that the US war against Iraq has fostered, the author addresses such questions as: what multilateralism and unilateralism are, when the US trend towards unilateralism emerged, how the US unilateralism can be explained, and whether multilateralism is synonymous with multipolarity. In addition, it considers which of both approaches is more efficient in order to achieve the challenge of global security. The author also criticizes the idealized view of multilateralism and analyzes its implications for Latin America.